Private ordering and the rise of terms of service as cyber-regulation - Luca Belli; Jamila Venturini (Internet Policy Review, 2016)
Online communications and activities require the intermediation of numerous private entities that unilaterally define and implement their terms of service (ToS). The substantive provisions set in the ToS regulate the relationships between intermediaries and users with a binding force that may be even stronger than the one exercised by the law. Notably, we stress that internet intermediaries privately enforce their contractual regulation by shaping the architecture of the networks and platforms under their control. Such regulation and implementation do not need to rely on "traditional" public law-enforcement mechanisms and may apply in a transnational fashion. This paper argues that internet governance is witnessing the increasing centralisation of power in the hands of internet intermediaries defining private orderings. While acknowledging that ToS are an efficient and well-suited instrument to regulate the online world, we claim that ToS unilaterally impose rules, despite being presented as voluntarily accepted by the involved parties through the expression of free and informed consent. Based on empirical research, we highlight that ToS and their private implementation affect internet users' capability to enjoy their human rights, with particular regard to freedom of expression (and innovation), the right to privacy and to due process. Lastly, we put forward some recommendations on internet intermediaries' compliance with human rights standards.
Keywords: 300; Terms of Service (TOS); Human rights